2007
DOI: 10.1074/jbc.m610318200
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive and Anti-angiogenic Sphingosine 1-Phosphate Receptor-1 Agonists Induce Ubiquitinylation and Proteasomal Degradation of the Receptor

Abstract: Sphingosine 1-phosphate (S1P), a multifunctional lipid mediator, regulates lymphocyte trafficking, vascular permeability, and angiogenesis by activation of the S1P 1 receptor. This receptor is activated by FTY720-P, a phosphorylated derivative of the immunosuppressant and vasoactive compound FTY720. However, in contrast to the natural ligand S1P, FTY720-P appears to act as a functional antagonist, even though the mechanisms involved are poorly understood. In this study, we investigated the fate of endogenously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
350
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 373 publications
(370 citation statements)
references
References 50 publications
15
350
0
5
Order By: Relevance
“…For this purpose, we used the FDA-approved drug FTY720 (fingolimod), which targets all S1P receptors except S1P 2 (7). FTY720 is a prodrug that is phosphorylated in vivo to form FTY720-P, which works as functional antagonist for the S1P 1 by inducing its internalization and degradation (11,36,37). Indeed, three consecutive days of treatment with FTY720 successfully reduced the expression of S1P 1 in microvascular fragments (Fig.…”
Section: Reversible and Size-selective Opening Of Bbb By Pharmacologicalmentioning
confidence: 96%
“…For this purpose, we used the FDA-approved drug FTY720 (fingolimod), which targets all S1P receptors except S1P 2 (7). FTY720 is a prodrug that is phosphorylated in vivo to form FTY720-P, which works as functional antagonist for the S1P 1 by inducing its internalization and degradation (11,36,37). Indeed, three consecutive days of treatment with FTY720 successfully reduced the expression of S1P 1 in microvascular fragments (Fig.…”
Section: Reversible and Size-selective Opening Of Bbb By Pharmacologicalmentioning
confidence: 96%
“…It was reported that S1P receptor agonists such as fingolimod and SEW2871 exert their effects by down-regulating S1P1 on the cell membrane [21][22][23]. We examined whether ONO-4641 also induces S1P1 down-regulation on the cell membrane.…”
Section: Ono-4641 Induces S1p1 Down-regulationmentioning
confidence: 99%
“…Fingolimod, a first-in-class S1P receptor agonist, has been approved recently for the treatment of relapsing MS. Fingolimod is a prodrug and phosphorylated reversibly to fingolimod-phosphate, the active moiety [11,12]. Fingolimod-phosphate activates S1P1 on lymphocytes via high-affinity receptor binding and subsequently induces S1P1 down-regulation on the cell membrane [21,22]. It is believed that down-regulation of S1P1 in lymphocytes by fingolimod-phosphate renders them unresponsive to the S1P gradient and prevents the egress from secondary lymphoid tissues [3,27,28].…”
Section: Group (No Of Animals)mentioning
confidence: 99%
“…FTY720 administration has proved beneficial in experimental disease models (19)(20)(21)(22)(23), and recently in human clinical trials of relapsing multiple sclerosis (24). Both S1P and FTY720 result in S1P1 internalization and recycling (25,26), FTY720 being a more efficient inducer of receptor degradation (27). This functional antagonism of S1P receptors leads to lymphocyte retention in lymphoid tissues, thus reducing the number of activated lymphocytes available to enter sites of inflammation, including the central nervous system (CNS) (28).…”
Section: Introductionmentioning
confidence: 99%